Women readers and writers in Argentina in the 1860s: Margarita Rufina Ochagavía y M. Sasor (Anclajes, 2011)
It is not exactly known how many women dared to write literature in Argentina during the second half of the nineteenth century. It is highly probable there were more than those registered in literary histories. While the more progressive intellectuals promoted a type of literature that would contribute to the progress of this young nation, that is, a literature useful and moral to educate both men and women, social prejudice against novels and women writers was renewed. Women who published stand out for having trespassed those barriers, for their deep need to write, to express their opinions and fantasies, and also for wanting to be acknowledged as writers. This paper presents two of the most forgotten ones:  Margarita Rufina Ochagavía, author of “An agel and a demon, or The value of a promise” (Un ángel y un demonio, o El valor de un juramento; 1857), and M. Sasor (Mercedes Rosas de Rivera), author of “María de Montiel: a Contemporary Novel” ( María de Montiel: Novela contemporánea; 1861) and “Emma or a Proscript's Daughter” (Emma o La hija de un proscripto; 1863), respectively. In particular, this paper examines the idea of novel they have, the readings they have done, the description of Argentine society present in their plots, and the ideological contents defended by both women.
Keywords: Margarita Rufina Ochagavía; Sasor (Mercedes Rosas de Rivera); women writers; Siglo XIX; argentine novel